2020
DOI: 10.1002/anie.201915254
|View full text |Cite
|
Sign up to set email alerts
|

Boron‐Induced Electronic‐Structure Reformation of CoP Nanoparticles Drives Enhanced pH‐Universal Hydrogen Evolution

Abstract: Even though transition‐metal phosphides (TMPs) have been developed as promising alternatives to Pt catalyst for the hydrogen evolution reaction (HER), further improvement of their performance requires fine regulation of the TMP sites related to their specific electronic structure. Herein, for the first time, boron (B)‐modulated electrocatalytic characteristics in CoP anchored on the carbon nanotubes (B‐CoP/CNT) with impressive HER activities over a wide pH range are reported. The HER performance surpasses comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
118
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(131 citation statements)
references
References 62 publications
7
118
0
Order By: Relevance
“…The Co 2p spectrum (Figure S3 a) can be decomposed into five peaks at 781.8, 797.5, 785.6, 787.5, and 803.1 eV. The former two peaks are corresponded to the Co 2p 3/2 and Co 2p 1/2 , respectively, while the other peaks are consistent with satellite bands [32] . The high‐resolution P 2p spectrum for the CoP@GF membrane (Figure S3 b) is split to three peaks at 129.7, 130.7, and 133.8 eV.…”
Section: Resultsmentioning
confidence: 95%
“…The Co 2p spectrum (Figure S3 a) can be decomposed into five peaks at 781.8, 797.5, 785.6, 787.5, and 803.1 eV. The former two peaks are corresponded to the Co 2p 3/2 and Co 2p 1/2 , respectively, while the other peaks are consistent with satellite bands [32] . The high‐resolution P 2p spectrum for the CoP@GF membrane (Figure S3 b) is split to three peaks at 129.7, 130.7, and 133.8 eV.…”
Section: Resultsmentioning
confidence: 95%
“…Notably, at the heterointerface of 1T‐MoS 2 and CoS 2 , both of the MoS 2 and CoS 2 side exhibit ultrahigh HER activity with almost zero Δ G H of −0.01 and −0.009 eV, which are even much smaller than state‐of‐art Pt catalyst of −0.08 eV. [ 28 ] It suggests that the heterointerface is the active center for HER, leading to ultrafast hydrogen adsorption/desorption kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…For Ni 3 S 4 , in light of the valence band theory, Ni‐3d orbitals overlap with 3p orbitals of ligand S atoms, resulting in (Ni–S) bonding bands and (Ni–S)* antibonding bands (Figure 1b). [ 19 ] The energy difference between (Ni–S) and (Ni–S)* is defined as charge transfer energy, which is depends on the electronegativity difference between Ni and S. [ 19b ] When heteroatoms with different atomic electronegativity are incorporated, the local electronic configuration and atomic arrangement of bonded Ni and adjacent S atoms can be reformed, [ 16,20 ] resulting in variable charge transfer energy, and consequently, the band position would shift as well.…”
Section: Adsorption Energy‐electronic Structure Relationshipmentioning
confidence: 99%
“…[ 15 ] Ren and co‐workers adopted electron‐deficient boron (B) as dopant to fine‐tuning the electron structure of CoP for balancing the rate H + reduction and removal of H 2 , and obtained B‐CoP catalyst achieves an ultralow overpotential at lager current density 100 mA cm −1 in both neutral and alkaline media. [ 16 ] Tan and co‐workers also reported that nonmetal doping can significantly boost the HER performance of Ni 3 Se 4 . [ 11b ] Thus, we rationally speculate that nonmetal doping can effectively reduce the energy barrier of the Volmer step and speed up the sluggish alkaline HER kinetics of Ni 3 S 4 .…”
Section: Introductionmentioning
confidence: 99%